FRP-reinforced masonry spandrels: Experimental campaign on reduced-scale specimens. (20th November 2020) - Sandoli, A.; Pacella, G.; Lignola, G.P.; Calderoni, B.; Prota, A.
Highlights: Experimental investigation on monotonic and cyclic behaviour of masonry spandrels reinforced by FRP. Twenty-four tests on H-shaped scaled specimens. Effect of different slenderness ratios on monotonic and cyclic behaviour. Different strengthening configurations to prevent brittle failure modes. Beneficial effect of some FRP configurations in term of strength, stiffness and ductility increases. Abstract: This paper deals with the experimental monotonic and cyclic behavior of masonry spandrels reinforced with Fiber Reinforced Polymers (FRP). The research is a part of a wider program, started by the authors in the last decade, regarding the analysis of the seismic behavior of masonry spandrels in historical buildings of the Mediterranean area. The paper summarizes the properties of the test units, the test set-up and the results of the experimental monotonic and cyclic behavior conducted on twenty-four scaled down H -shaped spandrels made with homogeneous material (e.g. mortar with low tensile strength). Both unreinforced and FRP-reinforced specimens with three different slenderness ratios – e.g. slender, intermediate and squat – and three different arrangements of FRP laminates have been considered for the tests. The main objective has been to verify the possibility of preventing brittle failure modes, typical of spandrels subjected to in-plane seismic actions (e.g. diagonal cracking), and of increasing their strength by applying specific reinforcement systems, so encouraging more ductile behavior characterized by toe-crushing at the ends of the spandrels itself.